Raman spectroscopy of tissue samples irradiated by protons - Synytsya, A; Alexa, P; Besserer, J; De Boer, J; Froschauer, S; Gerlach, R; Loewe, M; Moosburger, M; Obstová, I; Quicken, P; Sosna, B; Volka, K; et al. (International journal of radiation biology, 2004)
PURPOSE: Since the number of cancer patients treated by proton irradiation has increased in the last few years, it seems appropriate to study dose-dependent effects of proton irradiation on mammalian tissues in more detail. MATERIALS AND METHODS: Tissue samples of normal skin of mouse and swine, of a human tumour model xenograph, and of normal skin and a skin tumour (basal cell carcinoma) of a human patient of about 1 mm thickness were irradiated by 24 MeV protons (uniform delivered doses of 1, 7 and 50 Gy: skin of mouse and a human tumour model xenograph, and 0.5, 5 and 50 Gy: swine and human skin). Raman spectra of non-irradiated and irradiated samples were recorded and analysed. RESULTS: Amide I, P=O and C-O bond vibrations and aromatics were sensitive to the proton irradiation dose. In the C-H stretching region, the irradiation-mediated change of Raman spectra was significant only in the case of the skin tumour. CONCLUSIONS: It has been shown that Raman spectroscopy is suited to assess the radiation damage done to biological samples by protons. Proteins of the human skin tumour seem to be more sensitive to proton irradiation than proteins of normal human skin.
Keywords: transplantace nádorů; prasata; Swine; Transplantation, Heterologous; Neoplasm Transplantation; Spectrum Analysis, Raman; Ramanova spektroskopie; kůže; protony; Animals; lidé; ženské pohlaví; Skin; Humans; Protons; zvířata; myši; Mice; Female; transplantace heterologní